(untitled) (International Journal of Banking and Finance, 2024)
This study aims to determine the impact of the COVID-19 pandemic and government responses on the Malaysian stock market. Using the Kuala Lumpur Composite Index (KLCI) from 1st March 2020 to 31st December 2020, the study discovered several findings. First, the number of daily new COVID-19 cases affected the index. Nevertheless, the new cases turned out to be positive at a later stage. This finding inferred that investors grew apathetic towards COVID-19 over the long run. Second, daily new COVID-19 deaths negatively impacted the stock index. Third, the Movement Control Order (MCO) harmfully influenced the index. Fourth, the Recovery Movement Control Order RMCO and most government stimulus packages positively impacted the index. In conclusion, the government’s responses to COVID-19 have managed to mitigate several negative impacts of the pandemic on the stock market. The stimulus packages provided the much-needed impetus for market recovery during the pandemic.